Linguistic Metaphor of Time Concept in Kazakh Cognition - Beknazarova, U. (KU Publ., 2022)
This article aims to study the concept of Time as a complex linguistic phenomenon; analyze the formation process of the theory of Conceptual metaphor; describe its features, functions, and components. The theoretical background is based on the conceptual metaphor in a discursive picture of the world that has the relationship between language and culture. It demonstrates the motives for the development of understanding which helps to activate the mental and cognitive activity of the worldview. The leading research methods for this problem are mixed methods (qualitative and quantitative). Based on the survey results, we conclude that we live in a scroll time. As understanding conceptual metaphor and its meaning in the Kazakh language is deeply rooted in our modern society, we can say it is being connected to the modern culture we belong to. The materials of the article are of the practical and theoretical value for cross-cultural linguistic studies, including an educational process.
Қазақ танымындағы уақыт концептісінің тілдік табиғаты мен танымдық қызметі
Языковая природа и познавательная деятельность концепта времени в казахском познании
Keywords: concept; Kazakh cognition; time and space; universal; conceptual metaphor; culture and language; comparative analysis; discursive analysis